Raw Genomic Data: Storage, Access, and Sharing. Issue 1 (January 2018) - Shabani, Mahsa; Vears, Danya; Borry, Pascal
Abstract : Patients are increasingly being encouraged and supported to access and control their own medical and genomic data. We argue that well-established and transparent raw genomic data retention and returning policies are imperative to enable patients to practice their rights to access and control raw data.